Algunos poliquetos holoplanctónicos (Annelida: Polychaeta) del Parque Nacional Isla del Coco, Costa Rica - Jiménez-Cueto, Soledad; Suárez-Morales, Eduardo; Morales-Ramírez, Álvaro (Revista de Biología Tropical, 2012)
Some holoplanktonic polychaetes (Annelida: Polychaeta) from the Parque Nacional Isla del Coco, Costa Rica. The holoplanktonic polychaetes have not been surveyed in the oceanic waters adjacent to Isla del Coco. These pelagic forms are studied based on the analysis of zooplankton samples collected in the area. Samples were obtained both at night and daytime by standard plankton nets (0.2-0.5 mm meshes, 0.49 m mouth diameter) hauled horizontally and vertically off the oceanic island Isla del Coco, Costa Rica in the Eastern Tropical Pacific. Pelagic polychaetes were collected in one of the night samples and were taxonomically analyzed. The material obtained includes representatives of six species and five families: Alciopidae, Lopadorrhynchidae, Tomopteridae, Polynoidae, and Typhloscolecidae. Brief diagnoses, synonymies, comparative morphological comments, taxonomic illustrations, and data on the distribution of the species collected in the plankton of Isla del Coco are provided. The record of Drieschia pellucida Moore is the first of the species in the Eastern Tropical Pacific; our specimen shows some differences with respect to the original description. The rest of the species have been recorded previously in waters of the Eastern Tropical Pacific, but are the first records of this important protected area. Citation: Jiménez-Cueto, S., E. Suárez-Morales & Á. Morales-Ramírez. 2012. Algunos poliquetos holoplanctónicos (Annelida: Polychaeta) del Parque Nacional de Isla del Coco, Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 207-222. Epub 2012 Dec 01.